Seismic Fragility of Fixed and Flexible Base RC Bridge under Near-Fault Directivity Effects - Khurshid, Fahad Bin; Izhar, Md Shafquat; Islam, Nazrul; Khan, Nabeel Ahmed; Khan, Mohd. Bilal (Journal of the Civil Engineering Forum, 2026)
Reinforced Concrete bridges are widely used in highway infrastructure due to their cost-effectiveness and structural redundancy. However, they are highly vulnerable to seismic hazards, particularly in near-fault regions where ground motions exhibit extreme intensity and short-duration energy pulses. Near-fault ground motions are characterized by high-energy velocity pulses with long periods, pulse-like waveforms, and significant peak values, which can lead to severe structural damage. As modern design practices shift toward performance-based design, the vulnerability of bridges under these different types of near-fault ground motions have become an emerging area of interest for researchers and designers. However, a common practice is to assume fixed-base conditions for bridge piers during vulnerability assessments, which may lead to inaccurate results. The effect of assuming fixed-base conditions on the vulnerability assessment of bridge piers remains an open question. This study presents a comprehensive comparative analysis of seismic damage propagation in a simply supported multi-span RC bridge subjected to near-fault pulse-like ground motions with directivity effects. The bridge is modeled under two distinct foundation conditions: fixed-base and flexible-base, with the latter incorporating soil-structure interaction through a pile group foundation. The analytical framework employs Incremental Dynamic Analysis to develop seismic fragility curves, offering a thorough evaluation of the system-level performance. The results reveal that SSI significantly alters the structural response, with median normalized changes of approximately 27% in drift and 30% in base shear. In some cases, the normalized drift demand increased by up to 76.8%, whereas the normalized base shear decreased by up to 51.1%, indicating substantial shifts in deformation and force distribution. These variations significantly affect the energy dissipation capacity of the bridge, which is essential for mitigating damage progression and enhancing seismic resilience.